Evaluating the influence of feedback on motor skill learning and motor performance for children with developmental coordination disorder: a systematic review - Welsby, Ellana; Hordacre, Brenton; Hobbs, David; Bouckley, Joanne; Ward, Emily; Hillier, Susan (Frontiers in Pediatrics, 2024)
Children with developmental coordination disorder (DCD) have difficulties with learning and performing physical tasks. It is well known that task-specific practice is effective in improving motor skills. Additional feedback during practice may function as a quality improvement mechanism and therefore enhance motor skill outcomes. Aims: To investigate the effect of different forms of feedback on motor learning and motor performance in children with DCD. Methods: A systematic review was conducted (registration CRD42020175118) to investigate the effectiveness of different types of feedback, compared to other forms of feedback, or no additional feedback, on motor learning and motor performance outcomes in children with DCD. The search was run across six electronic databases (last search January 2024). Two reviewers independently screened studies for inclusion, assessed the quality of included studies, and extracted relevant data. A narrative synthesis was performed and included studies that assessed motor learning and/or performance outcomes following an intervention that delivered a specific form of feedback in comparison to another form of feedback or no specific feedback. Results: 14 articles from 13 trials were included in this review. Feedback was delivered by providing various forms of feedback, including: knowledge of results, focus of attention and augmented feedback delivered via technology. No significant differences were found between different forms of feedback for motor learning or performance outcomes for children with DCD. Interventions that used technology (with augmented feedback) to deliver the intervention were found to be as effective as traditional therapy. All groups who participated in therapy, regardless of the presence or type of feedback received, improved in overall scores on a motor performance outcome assessment. Conclusion: Despite the clear rationale for using feedback-oriented interventions for children with DCD, there is surprisingly limited and low-quality research. There is no clear evidence that one form of feedback is more effective than another, although it appears that feedback delivered via technology may be as effective as feedback delivered in traditional therapy interventions for children with DCD. Further exploration is required from appropriately powered and well-designed trials.